PROBLEM BASED LEARNING IN THE FACULTY OF MEDICINE – UNIVERSITY OF GEZIRA - abubakr, muzdalifa; Mirghani, Omer Ahmed; Mohamed, Mohamed Elsanousi (Gezira Journal of Health Sciences, 2007)
This article describes the main objectives of a medical school, how effective is problem based learning (PBL) in helping the student achieve the educational objectives of the faculty, the approach to PBL adopted by the Faculty of Medicine University of Gezira (FMUG).